Therapeutic potential of Licochalcone A in dermatological diseases: from basic to clinical research - Liu, Deming; Jiang, Xue; Yang, Fujin; Zhou, Jingjing; Li, Yanxi; Yang, Hua (Frontiers in Pharmacology, 2025)
Licochalcone A (Lico-A), a flavonoid compound extracted from Glycyrrhiza uralensis, exhibiting multiple pharmacological properties including anti-inflammatory, antibacterial, antioxidant, and antitumor effects. It demonstrates significant therapeutic potential in the field of dermatological treatment. This review focuses on the efficacy of Lico-A in the treatment of acne, atopic dermatitis, rosacea, pigmentation disorders, and skin tumors. Mechanistically, Lico-A targets multiple signaling pathways such as NLRP3 inflammasome, NF-κB, PLC/ERK/STAT3, AP-1, and Nrf2/HO-1, thereby modulating inflammatory cascades, oxidative stress, melanogenesis, and tumorigenic processes. Clinical studies have also confirmed its ability to reduce inflammatory lesions, improve skin barrier function, and suppressing hyperpigmentation. However, current research is limited by geographical bias, a lack of high-quality randomized controlled trials, and reliance on preclinical models. Future studies should focus on multicenter randomized controlled trials, advanced delivery systems, and mechanistic investigations using systems biology. Addressing these gaps could establish Lico-A as a multifunctional, evidence-based dermatologic therapy for inflammatory, infectious, and neoplastic skin disorders.